2016
DOI: 10.1111/odi.12507
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of orofacial manifestations in systemic sclerosis: a challenging management

Abstract: Systemic sclerosis (SSc) is a rare multisystem connective tissue disorder characterized by the triad fibrosis, vasculopathy and immune dysregulation. This chronic disease has a significant impact on the orofacial region that is involved in more than two-thirds of the cases. SSc patients can show a wide array of oral manifestations, which are usually associated with a severe impairment of the quality of life. They often present a decreased the salivary flow and a reduced mouth opening that contribute substantia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
74
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(81 citation statements)
references
References 151 publications
6
74
0
1
Order By: Relevance
“…This systematic study showed that the correlation between oropharyngeal features and quality of life of SSc patients was statistically significant. The findings provided by our literature review were in accordance with very recent reviews that studied oral manifestations and their treatments …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This systematic study showed that the correlation between oropharyngeal features and quality of life of SSc patients was statistically significant. The findings provided by our literature review were in accordance with very recent reviews that studied oral manifestations and their treatments …”
Section: Discussionsupporting
confidence: 91%
“…The findings provided by our literature review were in accordance with very recent reviews that studied oral manifestations and their treatments. 1,44,45 46 showed that patients were very concerned about their facial features. They also emphasised the issue of depression, which is an integral part of the overall management of these patients as there seems to be a strong link between facial appearance and feelings of depression and isolation.…”
Section: Discussionmentioning
confidence: 99%
“…In the article "The spectrum of orofacial manifestations in systemic sclerosis: a challenging management" (Jung, Martin, Schmittbuhl, & Huck, 2017), the authors have provided an excellent review drawing attention to the impact of the manifestations in the orofacial region of systemic sclerosis (SSc), a multisystem connective tissue disorder disease of a not well-known origin. We thank and congratulate the authors who pointed, in a concise and well-detailed report, the many issues related to this progressively high-profile disease.…”
Section: Dear Editormentioning
confidence: 99%
“…[14][15][16] SSc is more frequent and severe in African-Americans. 3,17,18 Dental and facial manifestations include: trismus (reduced interincisal distance) 19 ; secondary microstomia (reduced interlabial commissure distance) 20-22 ; dental caries [23][24][25][26] ; mask-like appearance; muscular atrophy; thin lips; xerostomia 19,25,27 ; rigidity with or without color change 28 of tongue and lips; periodontal ligament widening [29][30][31][32][33][34] ; periodontal attachment loss 26,35 ; trigeminal neuralgia [36][37][38] ; telangiectasia 19,39 ; oral mucosal/gingival fibrosis 2,40 ; gingival recession and stripping of attached gingiva 26,41 ; gastroesophageal reflux disease 42 ; temporomandibular disorders 43,44 and resorption of the angle of the mandible [45][46][47][48] ; as well as the coronoid process and the condyle. [49][50][51] The resorption has, on occasion, been so severe as to cause pathologic fracture of the mandible.…”
Section: Introductionmentioning
confidence: 99%
“…52 These condylar changes may result in the temporomandibular joint symptoms of clicking, popping, and crepitus. 43,44 19 Jung et al, 26 Baron et al, 22 Bajraktari et al 21 Microstomia 80%-90% DuBrul et al, 20 Bajraktari et al, 21 Baron et al 22 Mask-like cutaneous appearance 80%-90% Said et al, 19 Jung et al 26 Dental caries 3× Controls a Wood et al, 23 Baron et al, 22 Albilia et al, 42 Dagenais et al 50 Temporomandibular disorders 80%+ Ferreira et al, 43 Crincoli et al 44 Telangiectasia 70% Nagy et al, 39 Said et al, 19 Bajraktari et al 21 Periodontal ligament widening 30%-66% Marmary et al, 29 Auluck et al, 30 Krogh et al, 31 Anbiaee et al, 32 Jung et al, 26 Said et al, 19 Rowell et al 34 Gingival recession and stripping 2× Controls a Eversole et al, 41 Jung et al 26 Periodontal attachment loss 2x Controls a Pischon et al, 35 Jung et al, 26 Siefert et al, 33 Xerostomia 25%-71.2% Said et al, 19 Jung et al, 26 Nagy et al, 39 Chu et al, 25 Vincent et al, 27 Bajraktari et al 21 Mandibular resorption 8.6%-50% Auluck et al, 30 Rubin et al, 45 Doucet et al, 46 Pogrel et a...…”
Section: Introductionmentioning
confidence: 99%